Effortless Spontaneity The Dzogchen Commentaries by Nubchen Sangye Yeshe - Esler, Dylan (Brill, 2023)
The notion of effortlessness is central to the self-understanding of the Tibetan contemplative tradition known as Dzogchen. This book explores this key notion from a variety of perspectives, highlighting the distinctive role it plays in the Dzogchen approach's doctrinal architecture and meditative programme. The book's focus is on the early development of the Dzogchen tradition, especially as codified in a set of hitherto unstudied commentaries by the 10th-century scholar and meditation master Nubchen Sangye Yeshe. A full annotated translation of the commentaries is provided, along with an edition of the Tibetan texts on facing pages.